Kontestasi Hadis Azimat di Masyarakat Online - Syafi’ul Huda; Saifuddin Zuhri Qudsy (Universitas Nurul Jadid, 2019)
Indonesia is known as a multicultural nation, such as culture, ethnicity, religion or anything else. As a monotheistic religion, Islam does not necessarily accept the diversity of cultures it encounters in Indonesia. Regarding amulets for example, as objects of cultural heritage that are believed to have power, Islam underlines with a red thread. The reason is, with tiny objects that are very vulnerable to bring users in polytheism. In addressing this common thread, diverse views and attitudes of Muslims emerge. This article discusses the amulet contestation in an online society. From the search results, obtained several references in the form of the Prophet's hadith, atsar companions, and opinions of scholars related to this talisman. The first two references, present information on permissibility as well as a ban on the use of talismans. While the latter is more about explaining core vocabulary which is considered as the key to understanding this issue. In terms of contestation that occurs in online communities, there are four trends that can be used as a planner of their attitude; scientific data, the objectivity of assessment, insight about talismans, and how to express opinions. Each suggests there are mutual influences and self-existence. Then at the level of their understanding of the Islamic text that exists, those who are allergic to amulets only stop at the hadith that forbids it. They are reluctant to explore more information about other traditions or explanations than the traditions they hold as the other online communities do.Keywords: Contestation, Amulet, Online Society, and Understanding Of Religion.